Chicken chemerin alone or in mixture with adiponectin-visfatin impairs progesterone secretion by primary hen granulosa cells - Ophélie Bernardi; Mathias Fréville; Christelle Ramé; Maxime Reverchon; Joëlle Dupont (Poultry Science, 2024)
ABSTRACT: Adipokines including adiponectin (ADIPO), chemerin (CHEM) and visfatin (VISF) are involved in metabolism and reproductive functions. These 3 adipokines are present in ovarian cells in different preovulatory follicles in hens. We have previously shown that VISF and ADIPO are able to modulate in vitro steroid production by hen granulosa cells (GCs). It is, however, unclear whether CHEM acts on hen ovarian cells. In addition, no study has yet investigated the effect of a mixture of several adipokines such ADIPO, VISF, and CHEM on GCs from different preovulatory follicles. In this study, we investigated the effect of CHEM alone and in combination with ADIPO and VISF on cell viability, proliferation and progesterone secretion in cultured granulosa cells (GCs) from the largest follicles F1 and smaller ones (F3/F4) in the presence of gonadotropins (oLH and oFSH) or hIGF-1. First, various concentrations of chemerin were examined (0, 12, 25, 50, and 100 ng/mL) and then we determined the response to CHEM (at 25 ng/mL) in combination with ADIPO (10 µg/mL) and VISF (100 ng/mL). Chemerin exposure did not affect F1 and F3/F4 granulosa cell viability and proliferation whatever the concentation and in the presence of the mixture. However, it reduced progesterone secretion in dose dependent manner in both F1 and F3/F4 follicles. Furthermore, this CHEM inhibitory effect was significantly higher when CHEM was combined with ADIPO and VISF. Furthermore, CHEM reduced significantly oLH and oFSH- induced progesterone secretion in F1 GCs and oFSH and hIGF-1-induced progesterone secretion in F3/F4 GCs. Interestingly, this inhibitory effect of CHEM was similar in F1 GCs when CHEM was in mixture with ADIPO and VISF whereas it was significantly higher in F3/F4 GCs. Taken together, CHEM impairs progesterone secretion in cultured hen GCs and this inhibitory effect can be potentiated when it is in combination with other adipokines.